ANALYSIS OF THE DECLINE IN OUTPATIENT VISITS TO THE OB-GYN CLINIC AT PANTI WALUYA HOSPITAL MALANG - Lionardy, Chandra; Setya Wardani, Diadjeng; setiawati, Lisa (Journal of Community Health and Preventive Medicine, 2025)
Maternal and newborn health is a key indicator of societal well-being. Mothers’ awareness of the importance of antenatal care at obstetrics and gynecology (ob-gyn) services plays a crucial role in ensuring maternal health during pregnancy, childbirth, and the postpartum period. Such awareness indirectly contributes to increased patient visits. This study aims to analyze the causes of the low number of outpatient visits to the ob-gyn clinic, which may serve as a basis for future hospital strategies. A qualitative case study approach was employed, utilizing unstructured interviews and brainstorming sessions for data collection. Root cause analysis was conducted using a fishbone (Ishikawa) diagram, followed by literature review and further discussions to develop potential solutions. The findings reveal that the decline in outpatient visits to the ob-gyn clinic at a private hospital is attributed to the absence of a structured marketing plan and the suboptimal promotion of ob-gyn priority services on social media. The hospital’s strategies to increase clinic visits include regularly promoting hospital facilities, ensuring accessible information about available services, highlighting ob-gyn priority services, and establishing partnerships with primary healthcare facilities. Promoting ob-gyn priority services through social media and within the hospital environment is expected to increase patient visits, ultimately contributing to the hospital’s revenue growth.